Biolimus-eluting stent with biodegradable polymer improves clinical outcomes in patients with acute myocardial infarction. Issue 4 (25th November 2014) - Zhang, Yao-Jun; Iqbal, Javaid; Windecker, Stephan; Linke, Axel; Antoni, Diethmar; Sohn, Hae Young; Corti, Roberto; van Es, Gerrit-Anne; Copt, Samuel; Eerdmans, Pedro; Saitta, Rana; Morice, Marie-Claude; et al.
Abstract : Objective: To investigate clinical outcomes of coronary intervention using a biolimus-eluting stent (BES) compared with a sirolimus-eluting stent (SES) in patients with acute myocardial infarction (AMI) in the L imus E luted from A D urable versus ER odable Stent (LEADERS) coating trial at the final 5-year follow-up. Methods: The LEADERS trial is a multicentre all-comer study, where patients (n=1707) were randomised to percutaneous intervention with either BES containing biodegradable polymer or SES containing durable polymer. Out of 1707 patients enrolled in this trial, 573 patients had percutaneous coronary intervention for AMI (BES=280, SES=293) and were included in the current analysis. Patient-oriented composite endpoint (POCE, including all death, all myocardial infarction (MI) and all revascularisations), major adverse cardiac events (MACE, including cardiac death, MI and clinically indicated target vessel revascularisation) and stent thrombosis were assessed at 5-year follow-up. Results: The baseline clinical, angiographic and procedural characteristics were well matched between BES and SES groups. In all patients with AMI, coronary intervention with a BES, compared with SES, significantly reduced POCE (28.9% vs 42.3%; relative risk (RR) 0.61, 95% CI 0.47 to 0.82, p=0.001) at 5-year follow-up. There was also a reduction in MACE rate in the BES group (18.2% vs 25.9%; RR 0.67, 95% CI 0.47 to 0.95, p=0.025); however, there was no difference in cardiac death and stent thrombosis. In patients with ST-elevation MI (STEMI), coronary intervention with BES significantly reduced POCE (24.4% vs 39.3%; RR 0.55, 95% CI 0.36 to 0.85, p=0.006), MACE (12.6% vs 25.0%; RR 0.47, 95% CI 0.26 to 0.83, p=0.008) and cardiac death (3.0% vs 11.4%; RR 0.25, 95% CI 0.08 to 0.75, p=0.007), along with a trend towards reduction in definite stent thrombosis (3.7% vs 8.6%; RR 0.41, 95% CI 0.15 to 1.18, p=0.088), compared with SES. Conclusions: BES, compared with SES, significantly improved safety and efficacy outcomes in patients with AMI, especially those with STEMI, at 5-year follow-up. Trial registration number: NCT 00389220.